EFFICACY OF GP-11 KHV DNA VACCINE IN Cyprinus carpio koi - Sekar Ayu Chairunnisa; Sri Nuryati; Alimuddin Alimuddin; Sri Murtini; Ayi Santika; Dwi Hany Yanti (Indonesian Aquaculture Journal, 2016)
Koi herpesvirus (KHV) is one of the major pathogen for koi and common carp which cause high mortality and economic losses for the farmer. The purpose of this study was to determine the efficacy of glycoprotein-11 (GP-11) KHV DNA vaccine and compared to GP-25 KHV DNA vaccine. The vaccine in the form of naked DNA plasmidwas delivered by intramuscularly injection to the 3-month-old koi. The fish were divided into six groups, i.e. unvaccinated group (negative control C- and  positive control C+), and vaccinated group (2.5 μg/100 μl of GP-11 (group 1), 7.5 μg/100 μl of GP-11 (group 2), 12.5 μg/100 μl of GP-11 (group 3), and 12.5 μg/100 μl of GP-25 (group 4)). At day 42 post vaccination, all fish of each groups were challenged by injecting KHV titre 10-3 FID50. Number of dead fish was counted everyday after the challenge until 30 days. The results showed that vaccinated fish were had survival rate of 83.33-93.33% (group 2, 3 and 4). It’s show that GP-11 KHV DNA vaccine has high efficacy. As conclusion, GP-11 DNA vaccine could be an alternative DNA vaccine for preventing KHV infection.